2019
DOI: 10.1111/idj.12462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-carious cervical lesions among the general population of the Republic of Srpska, Bosnia and Herzegovina

Abstract: Introduction As non‐carious cervical lesions (NCCLs) may compromise aesthetics and function, knowledge of their aetiological covariables enhances management of clinical complaints and success of restorative treatments. Aims The primary aim of this study was to assess the presence of NCCLs among the general population of the Republic of Srpska, Bosnia and Herzegovina and the potential association with patient‐related risk factors. Methods A prevalence study of NCCLs included 738 respondents from eight towns/mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2
14

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 44 publications
1
38
2
14
Order By: Relevance
“…However, a recent clinical trial with patients between 18 and 40 years old treated for NCCLs and cervical dentin hypersensitivity at a Brazilian university revealed a prevalence of 88.1% and also suggested an increasing distribution of NCCLs among youths [1]. Other studies reported prevalence ratios below 53% [19][20][21][22][23]. The bivariate regression analysis revealed that daily training time is a dominant risk indicator for the development of NCCLs.…”
Section: Discussionmentioning
confidence: 90%
“…However, a recent clinical trial with patients between 18 and 40 years old treated for NCCLs and cervical dentin hypersensitivity at a Brazilian university revealed a prevalence of 88.1% and also suggested an increasing distribution of NCCLs among youths [1]. Other studies reported prevalence ratios below 53% [19][20][21][22][23]. The bivariate regression analysis revealed that daily training time is a dominant risk indicator for the development of NCCLs.…”
Section: Discussionmentioning
confidence: 90%
“…As LCNC vem aumentando com o passar dos anos, devido a alguns fatores e principalmente à prolongada expectativa de vida dos pacientes, ainda podemos destacar que seu diagnóstico é complexo (JAKUPOVIC et al, 2010) Herzegovina a prevalência de LCNC foi de 52% (ZUZA et al, 2019). Em um grupo de 1320…”
Section: Discussionunclassified
“…Certamente esses resultados se devem a prolongada exposição dos pacientes a fatores causais a longo prazo (KOLAK et al, 2018;TEIXEIRA et al 2020). Zuza et al (2019) ainda destaca que a menor prevalência de LCNC é em pacientes com menos de 20 anos de idade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As LCNCs, geralmente, são ocasionadas por fatores, como: biocorrosão (químicos, bioquímicos e degradação eletroquímica); ácidos, tanto de forma intrínseca como extrínseca; desgaste causado pela escovação traumática; hábitos parafuncionais; oclusão traumática e excesso de carga oclusal sobre um dente 2,3 .…”
Section: Introductionunclassified